E-learning in Belgium: a case study of Mons University - Pokrzycka, Lidia (International Journal of Educational Innovation and Research, 2024)
The implementation of e-learning in higher education in some European countries is a real challenge. Academics still face resistance from university authorities to launching e-learning centres because of the costs, but they also do not see the point of investing in an inferior type of didactics (they believe that it is impossible to teach effectively online, only possibly in crisis situations such as a pandemic). It turns out that e-learning in the form of bottom-up initiatives was already being organised many years ago in Belgium, for example, and the results have led university authorities to take an interest in investing in e-learning.  The aim of the article is to present the innovations implemented at the Belgian university, with particular regard to open e-learning courses. The research is based on participant observation, interviews with employees from the team introducing e-learning at the Belgian university, as well as on source materials from the visited higher education institution. The publication demonstrates that it is possible to implement professional e-learning from scratch, even without substantial support from the university authorities. The research shows that it is possible to implement effective online courses, targeting lecturers, students and external audiences, thanks to innovators who want to implement modern educational methods, while improving their own skills all the time.